Tashmīmu al Manhaj al Dirōsī li Ta’līmi Mahāroti al Kalām ‘ala Asāsi Ta’līmi al Mufrodāt - Rifqi, Mohammad Rifqi Junaidi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Abstract              Al Beer Pandaan Pasuruan Islamic boarding school is one of the educational institutions that teaches Arabic. Arabic language teaching at this institution focuses on learning grammar and learning speaking skills. The teaching of Arabic grammar in it was considered successful in its implementation, because it received a lot of enthusiasm from the director of the institution and the administrators of the boarding school. This is different from speaking skills which are considered less successful. Based on observations of the problem and needs analysis carried out by researchers regarding the teaching of speaking skills, several problems were found, including (1) the learning foundation is not appropriate (2) students do not have vocabulary reserves that they will use in the speaking process. (3)The education system is ineffective. (4) Students are less interested in speaking Arabic.             Referring to this problem, the researcher will design a curriculum to teach speaking skills at the Al Beer Pandaan Pasuruan Islamic boarding school using a vocabulary memorization approach. As is known, vocabulary has an important role in the development of speaking skills.             The researcher used a research and development approach by following the steps suggested by J. Yalden in developing educational programs. The results of the research are: Curriculum for teaching speaking skills with mufrodat memorization activities which contain learning objectives, indicators, lesson materials, teaching activities, evaluation, methods, time and learning activities. Meanwhile, the results of the validity test, experts see that the designed curriculum has "good" results. Very easy to use in the process of teaching speaking skills.                                                                   Keywords: Curriculum, speaking skills, vocabulary teaching